Hubungan Antara Stres Kerja Dan Lingkungan Kerja Dengan Organizational Citizenship Behaviour (OCB) Di Industri Manufaktur PT.X Surabaya: THE RELATIONSHIP BETWEEN JOB STRESS AND WORK ENVIRONMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN THE MANUFACTURING INDUSTRY PT.X SURABAYA - Wibowo, Aldi (Psikodinamika: Jurnal Literasi Psikologi, 2025)
This study aims to analyze the relationship between work stress and work environment on Organizational citizenship behaviour (OCB) at PT X Surabaya. Based on multiple linear regression analysis, it was found that work stress and work environment have a positive relationship with OCB. These results indicate that the higher the level of work stress and work environment, the higher the employees' OCB, and vice versa. A significance value of 0.000 (p < 0.005) indicates that work stress has a significant effect on OCB, supporting the hypothesis that work stress and work environment can be predictors of OCB behaviour. The study also notes that the OCB category of employees tends to increase in line with the high work stress category and a moderate work environment category. However, the relationship between OCB and the work environment did not show very strong results, which is suspected to be due to other factors not measured in this study. Risk factors such as a comfortable work environment, social support, and appropriate workload also influence OCB behaviour, as explained in previous studies. These findings support previous research stating that work stress and work environment significantly affect OCB. This study provides an important contribution to understanding the factors influencing OCB, with practical implications for employee management in the workplace.